Predictors of recurrence, early treatment failure and death from Staphylococcus aureus bacteraemia: observational analyses within the ARREST trial - Szubert, AJ; Bailey, SL; Cooke, GS; Peto, T; Llewelyn, MJ; Edgeworth, JD; Walker, AS; Thwaites, GE (Elsevier, 2019)
Objectives: Adjunctive rifampicin did not reduce failure/recurrence/death as a composite endpoint in the ARREST trial of Staphylococcus aureus bacteraemia, but did reduce recurrences. We investigated clinically-defined 14-day treatment failure, and recurrence and S. aureus-attributed/unattributed mortality by 12-weeks to further define their predictors.